Pekan Siaga Bencana Pada ABK Di SLB Manunggal Slawi - Sari, Dewi Puspita; Priratmaningtyas, Ika Wahyu; Sari, Komala; Afifah, Ismi Nur; Halisa, Halisa; Astuti, Tri; Halisa, Nely Nur (Efektor, 2020)
Abstract Pekan Siaga Bencana Pada Anak Berkebutuhan Khusus (ABK) is a program to address issues facing children with special needs at SLB Manunggal Slawi. The purpose of this study is to learn the development of special needs knowledge and skills of children through the online disaster alert program by training children with specific needs on disaster alert through zoom and youtube applications; Training children with specific needs to act quickly in self-defense through zoom's applications; Giving special needs to kids on disaster alert via zoom and youtube apps. The method used in this study is a qualitative study method. The data-gathering technique used is participation observations made through zoom teleconferences applications performed by researchers with children with special needs. The study is carried out in August 2020. Through the disaster preparedness week program, the knowledge and skills of ABK about disasters have increased. This program is a sound success and can be used as a model for others in carrying out disaster preparedness education for children with special needs online